2019
DOI: 10.4102/sajcd.v66i1.637
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated prenatal and perinatal risk factors for oropharyngeal dysphagia in high-risk neonates in a South African hospital

Abstract: BackgroundThe prevalence of neonatal oropharyngeal dysphagia (OPD) in high-risk infants in lower-middle-income countries is unknown.ObjectivesTo determine the prevalence and associated risks for OPD in high-risk neonates in order to allow timely intervention for OPD, minimising negative outcomes.MethodA prospective cross-sectional observational study was conducted in an urban hospital in South Africa. Clinical feeding assessments were conducted using the Neonatal Feeding Assessment Scale with all available neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…A positive correlation between the prolonged duration of mechanical ventilation (> 5 days) and dysphagia was also demonstrated by Brodsky et al (17). Da Costa et al showed significant correlations between neonatal dysphagia with neurological complications and low birth weight (< 2500 g) (14). Jadcherla also observed that neonatal feeding skills were significantly affected by birth weight (7).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A positive correlation between the prolonged duration of mechanical ventilation (> 5 days) and dysphagia was also demonstrated by Brodsky et al (17). Da Costa et al showed significant correlations between neonatal dysphagia with neurological complications and low birth weight (< 2500 g) (14). Jadcherla also observed that neonatal feeding skills were significantly affected by birth weight (7).…”
Section: Discussionmentioning
confidence: 73%
“…Although very few investigations reported the prevalence rate of swallowing complications among infants with a history of intubation, different prevalence rates were reported among other population studies. Da Costa et al demonstrated that of 81 high-risk newborns, 64.2% had dysphagia (14). An investigation by Hoffmeister et al showed that of 372 patients aged 0 -16 years, 29% had dysphagia after extubation.…”
Section: Discussionmentioning
confidence: 99%
“…Rhoda et al ( 2018 ) suggested that some of these deaths may be preventable by ensuring that feeding guidelines, including breastfeeding and safe feeding methods, are explained and demonstrated to caregivers prior to discharge from the hospital. Furthermore, local research suggests that infants return to medical facilities post-discharge with feeding difficulties, which can result in serious complications such as aspiration, poor weight gain and malnutrition (Da Costa et al, 2019 ). This highlights the need for a coordinated and comprehensive approach to screening, assessment and intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Given the complexity of cases and the NICU environment, it is vital to adopt a multidisciplinary approach to assessment and intervention, with caregivers at the centre of the team (Barbosa, 2013 ; Da Costa et al, 2019 ). Other team members include but are not limited to doctors, neonatal nurses and other developmental professionals including physiotherapists, occupational therapists, dieticians, social workers, psychologists and speech-language therapists (SLTs).…”
Section: Introductionmentioning
confidence: 99%
“…DaCosta, Krüger, Kritzinger and Graham reported an unexpectedly high prevalence of 64% (52 of total 81 babies) of neonatal oropharyngeal dysphagia (OPD) in high risk neonates in a South African Hospital who were deemed medically stable and ready to feed orally indicating the need for assessment and management by Speech Language Pathologists (SLPs). 1 A significant percentage of neonates, have difficulty in swallowing due to maturational issues due to prematurity, low birth weight; anatomic malformations such as craniofacial birth defects such as cleft lip and palate (CLP) and Pierre Robin Sequence (PRS); neurogenic factors such as Hypoxic Ischemic Encephalopathy (HIE). Necrotizing Enterocolitis (NEC), GERD, chronic multisystem illness, sepsis and metabolic disease, structural abnormalities of the brain.…”
Section: Introductionmentioning
confidence: 99%